The role and functions of family museums in family education of university students - Galkina, Tatiana W. (Oficyna Wydawnicza ATUT - Wrocławskie Wydawnictwo Oświatowe, 2012)
The article is concerned with identification of the educational influence of the family museums on contemporary youth. The conclusions presented in the article are based on the results of a survey conducted in one of the departments of Tomsk State Pedagogical University. The research allowed for the identifi cation of the functions of family museums (security-related, axiological, exploratory, informational and cognitive, communicational, recreational, and aesthetic functions), which influence the process of the education of an individual.
Keywords: home museum; family; upbringing